The Effects of Metalinguistic Written Corrective Feedback (WCF) on Language Preparatory School Students` TOEFL Independent Writing Section Score - Soran Abubakr Abdulrahman; Saban Kara (International Journal of Social Sciences & Educational Studies, 2022)
Varied feedback strategies are prevalent to enhance learners` skills in an Academic Writing course. However, there has been an ongoing discussion on classifying one as the most efficient strategy. In this regard, this study investigated the impacts of metalinguistic feedback on the TOEFL IBT Independent Writing Section Score of language preparatory school students over 12 weeks using pre-test and post-test. Initially, 40 students were separated into two groups through simple random sampling method. Experimental group followed the regulations of metalinguistic feedback strategy, whereas control group students were exposed to direct feedback throughout the study. Each student wrote 6 essays to improve their writing skills. Additionally, their feedback type was arranged according to their groups. IBM SPSS 23. was employed to analyze quantitative data through independent and paired samples t test. It was measured that students in experimental group increased their success rate significantly by considering .000 p-value in independent and paired samples t test respectively. However, no significant improvement was noticed in control group. Likewise, the questionnaire and interview analysis confirmed that metalinguistic feedback was more effective than direct feedback. Findings of this study suggest that metalinguistic feedback strategy can increase students` motivation and enthusiasm so that the learners can boost their performance in Academic Writing courses.